Changes in renal function with long‐term exposure to antiretroviral therapy in HIV‐infected adults in Asia. Issue 11 (24th September 2018) - Joshi, Kedar; Boettiger, David; Kerr, Stephen; Nishijima, Takeshi; Van Nguyen, Kinh; Ly, Penh Sun; Lee, Man Po; Kumarasamy, Nagalingeswaran; Wong, Wingwai; Kantipong, Pacharee; Cuong, Do Duy; Kamarulzaman, Adeeba; et al.
Abstract: Purpose: Renal disease is common among people living with human immunodeficiency virus (HIV). However, there is limited information on the incidence and risk factors associated with renal dysfunction among this population in Asia. Methods: We used data from the TREAT Asia HIV Observational Database. Patients were included if they started antiretroviral therapy during or after 2003, had a serum creatinine measurement at antiretroviral therapy initiation (baseline), and had at least 2 follow‐up creatinine measurements taken ≥3 months apart. Patients with a baseline estimated glomerular filtration rate (eGFR) ≤60 mL/min/1.73 m 2 were excluded. Chronic kidney disease was defined as 2 consecutive eGFR values ≤60 mL/min/1.73 m 2 taken ≥3 months apart. Generalized estimating equations were used to identify factors associated with eGFR change. Competing risk regression adjusted for study site, age and sex, and cumulative incidence plots were used to evaluate factors associated with chronic kidney disease (CKD). Results: Of 2547 patients eligible for this analysis, tenofovir was being used by 703 (27.6%) at baseline. Tenofovir use, high baseline eGFR, advanced HIV disease stage, and low nadir CD4 were associated with a decrease in eGFR during follow‐up. Chronic kidney disease occurred at a rate of 3.4 per 1000 patient/years. Factors associated with CKD were tenofovir use, old age, low baseline eGFR, low nadir CD4, and protease inhibitor use. Conclusions: There is an urgent need to enhance renal monitoring and management capacity among at‐risk groups in Asia and improve access to less nephrotoxic antiretrovirals.